2016
DOI: 10.1093/nutrit/nuv108
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and cord blood vitamin D status and childhood infection and allergic disease: a systematic review

Abstract: Context: It is unclear how in utero vitamin D deficiency affects the extraskeletal health of children, despite the known risks for adverse pregnancy/birth outcomes. Objective: This systematic review seeks to assess the effect of in utero vitamin D exposure on childhood allergy and infection outcomes using the PRISMA guidelines. Data Sources: MEDLINE, Cochrane Library, and Web of Science databases were searched. Study Selection: Literature published through April 2015 was searched for studies reporting on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 82 publications
1
9
2
Order By: Relevance
“…Similar results in adults were reported by Jolliffe et al [126]. Some SRs on prenatal vitamin D status (assessed by maternal or cord blood 25(OH)D mainly derived from birth cohort studies) and ARI reported mixed results [71,74,126,128]. In the MA by Pacheco-Gonzalez et al, the pooled odds ratio for ARI in the offspring was 0.64 (95% CI 0.47 to 0.87) when comparing the highest with the lowest 25(OH)D category [74], whereas there was no significant result for such an association in the MA by Feng et al [71].…”
Section: Primary Preventionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similar results in adults were reported by Jolliffe et al [126]. Some SRs on prenatal vitamin D status (assessed by maternal or cord blood 25(OH)D mainly derived from birth cohort studies) and ARI reported mixed results [71,74,126,128]. In the MA by Pacheco-Gonzalez et al, the pooled odds ratio for ARI in the offspring was 0.64 (95% CI 0.47 to 0.87) when comparing the highest with the lowest 25(OH)D category [74], whereas there was no significant result for such an association in the MA by Feng et al [71].…”
Section: Primary Preventionsupporting
confidence: 82%
“…In our search for SRs on vitamin D and ARI, we identified 14 records [71,74,77,100,[126][127][128][129][130][131][132][133][134][135]; of which five reported data on cohort studies; [71,74,100,126,128] and 11 included MAs from RCTs [77,100,126,127,[129][130][131][132][133][134][135] (Supplemental Tables S10-S13 and Figure S3). Using AMSTAR 2 as an instrument for assessing methodological quality, 8 of the 14 SRs that examined the association between vitamin D and the prevention or treatment of ARI can be categorised as high quality; three studies were categorised as medium quality; and the other two studies as low and very low quality, whereas AMSTAR 2 was not developed to assess the quality of the only IPD MA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review by Fried et al. and a meta‐analysis by Beckhaus et al. concluded that higher maternal intake of vitamin D was associated with lower risk of offspring wheeze; however, no associations were found for other allergy outcomes.…”
Section: Individual Immunomodulatory Nutrient Intakementioning
confidence: 99%
“…Vitamin 25(OH)D deficiency results primarily from unawareness that moderate sun exposure constitutes the principal source of vitamin D3 in most humans [2]. The active form of vitamin D, i.e., 1,25(OH) 2 D, is now recognized as an important hormone playing a crucial role in skeletal homeostasis (classical effects) and exerting non-classical effects in various pathological and physiological conditions, such as cancer, arterial hypertension, cardiovascular diseases, brain development and immunomodulation [3,4,5,6]. …”
Section: Introductionmentioning
confidence: 99%